Large-scale human environmental intervention is related to a richness reduction in Mexican odonates - Karina Cuevas-Yáñez; Mariana Benítez; Maya Rocha; Alex Cordoba-Aguilar (Revista Mexicana de Biodiversidad)
It is unclear how land use change, reduction in tree cover and human footprint impact species occurrence and co-occurrence especially at a large regional scale. This is particularly prevalent for species with complex life cycles, for example odonates (dragonflies and damselflies). We evaluated richness of odonates in Mexico in terms of land use, tree cover and human footprint. We also analyzed how odonate species co-occur to interpret our richness analysis using a community perspective. We used odonate collecting records from year 2000 to 2014. Odonate geographical records were more abundant in forest and agricultural areas, and decreased in areas without vegetation. Although our results may suffer of incomplete samplings, there was a positive relationship between species richness and tree cover, and a quadratic relationship with human footprint was observed. These results indicate that some degree of forest disturbance may still sustain relatively high odonate richness levels. Finally, species tend to co-occur in particular ensembles with some species being key in their ecological communities. Further studies should detail the role these key species play in their environments to provide community stability.